Field Assessment of Some Local Cowpea Rhizobium Inoculants. - Oloke, Julius Kola (Obafemi Awolowo University, 2014)
The effectiveness of lignite, sub-bituminous, cow manure and peat as rhizobia carriers and inoculants were assessed in a field plot. The inoculants prepared by incorporating each of three rhizobia strains (IFE CR9, IFE CR15 and R. japonicum) into each of the carrier materials were used to inoculate three cowpea varieties viz. TVU 1190, IT82E-60 and Ife brown.